2011
DOI: 10.1177/0192623311424169
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Long-Term Preclinical Safety Evaluation of Two Glatiramoid Compounds (Glatiramer Acetate, Copaxone®, and TV-5010, Protiramer) in Rats and Monkeys

Abstract: Glatiramer acetate (GA), the active ingredient in Copaxone 1 , is a complex mixture of polypeptides used for the treatment of relapsing remitting multiple sclerosis. Glatiramoids are related mixtures that may differ in some characteristics of the prototype molecule. Our aim is to describe the long-term toxicity studies with protiramer (TV-5010), a new glatiramoid, in comparison with similar studies conducted with GA. The toxicity of twice-weekly subcutaneous injections of protiramer to Sprague-Dawley rats (twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 30 publications
3
34
0
1
Order By: Relevance
“…As described below, TV-5010 showed severe toxicity in long-term preclinical studies that was never seen with GA (Ramot et al 2012).…”
Section: Glatiramer Acetatementioning
confidence: 96%
See 3 more Smart Citations
“…As described below, TV-5010 showed severe toxicity in long-term preclinical studies that was never seen with GA (Ramot et al 2012).…”
Section: Glatiramer Acetatementioning
confidence: 96%
“…Like other NBCDs, GA does not have a homo-molecular structure, and the GA in Copaxone ® is defined in large part by its well-controlled manufacturing process, which was developed and has been optimized by the manufacturer (Teva Pharmaceutical Industries, Ltd.) over the last few decades (Duncan and Gaspar 2011;Nicholas 2012;Schellekens et al 2011;Varkony et al 2009). The importance of the stringent manufacturing method used to create GA is exemplified by development of a second generation GA glatiramoid known as TV-5010 that the same manufacturer prepared by making slight changes to the GA manufacturing process conditions at downstream stages (Ramot et al 2012). The product had the same molar ratio of AA as GA but a higher average molecular weight (MW).…”
Section: Glatiramer Acetatementioning
confidence: 99%
See 2 more Smart Citations
“…In fact, by slight alteration of the manufacturing process, Teva had produced a glatiramoid (TV-5010) that was similar in terms of amino acid ratio and physical properties [13] to Copaxone ® . While good safety and tolerability in patients treated with TV-5010 was shown, long-term toxicity studies in rats and monkeys revealed the occurrence of fi brosis in rats and eosinophilia in monkeys.…”
Section: Special Reportmentioning
confidence: 99%